Complexity of the Microglial Activation Pathways that Drive Innate Host Responses During Lethal Alphavirus Encephalitis in Mice - Nilufer Esen (ASN Neuro, 2012)
Microglia express multiple TLRs (Toll-like receptors) and provide important host defence against viruses that invade the CNS (central nervous system). Although prior studies show these cells become activated during experimental alphavirus encephalitis in mice to generate cytokines and chemokines that influence virus replication, tissue inflammation and neuronal survival, the specific PRRs (pattern recognition receptors) and signalling intermediates controlling microglial activation in this setting remain unknown. To investigate these questions directly in vivo , mice ablated of specific TLR signalling molecules were challenged with NSV (neuroadapted Sindbis virus) and CNS viral titres, inflammatory responses and clinical outcomes followed over time. To approach this problem specifically in microglia, the effects of NSV on primary cells derived from the brains of wild-type and mutant animals were characterized in vitro. From the standpoint of the virus, microglial activation required viral uncoating and an intact viral genome; inactivated virus particles did not elicit measurable microglial responses. At the level of the target cell, NSV triggered multiple PRRs in microglia to produce a broad range of inflammatory mediators via non-overlapping signalling pathways. In vivo , disease survival was surprisingly independent of TLR-driven responses, but still required production of type-I IFN (interferon) to control CNS virus replication. Interestingly, the ER (endoplasmic reticulum) protein UNC93b1 facilitated host survival independent of its known effects on endosomal TLR signalling. Taken together, these data show that alphaviruses activate microglia via multiple PRRs, highlighting the complexity of the signalling networks by which CNS host responses are elicited by these infections.